2013
DOI: 10.2217/fmb.13.84
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Immunological Function of the Cryptococcus Neoformans Capsule

Abstract: The encapsulated fungal pathogen Cryptococcus neoformans represents a significant agent of life-threatening infections in immunocompromised subjects. A unique characteristic of Cryptococcus species is the presence of a polysaccharide capsule, which is essential for virulence and endows Cryptococcus with potent immunoregulatory properties. This review provides an overview of the immunological properties of the principal components of C. neoformans capsule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 85 publications
1
71
0
2
Order By: Relevance
“…Furthermore, GXM shed from cells during infection interferes with immune cell function. 14,15 Similar to what is seen in mammals, capsule size increases during G. mellonella infection and increased capsule size in correlated with reduced phagocytosis by hemocytes. 16 In the present study, the authors find that capsule and GXM have an effect on lytic activity of the larval hemolymph, a humoral immune response of G. mellonella.…”
supporting
confidence: 53%
“…Furthermore, GXM shed from cells during infection interferes with immune cell function. 14,15 Similar to what is seen in mammals, capsule size increases during G. mellonella infection and increased capsule size in correlated with reduced phagocytosis by hemocytes. 16 In the present study, the authors find that capsule and GXM have an effect on lytic activity of the larval hemolymph, a humoral immune response of G. mellonella.…”
supporting
confidence: 53%
“…Subsequent studies showed that GXM activates SHIP via surface Fc␥RIIb receptors. Active SHIP then blocks the recruitment of MyD88 (myeloid differentiation primary response gene 88) and Akt, thereby impeding IB␣ phosphorylation and degradation (11,12). These data imply that GXM would block LPS-induced nuclear accumulation of p65-containing NF-B dimers, thereby preventing the NF-B-dependent production of pro-inflammatory cytokines.…”
Section: Gxm Attenuates Lps-induced Nuclear Translocation Of Nf-b-mentioning
confidence: 95%
“…These effects can be explained, at least in part, by the ability of GXM to subvert the activity of the NF-B signaling pathway (reviewed in Ref. 12).…”
mentioning
confidence: 99%
“…This complex structure is composed mainly of polysaccharides that are linked to the cell wall (102). Mutant strains unable to synthesize a capsule are avirulent, and the capsular polysaccharides exert profound depressive effects on both innate and adaptive immune responses (103,104). Different factors, including pH, have been shown to influence the capsule size and structure (105).…”
Section: Ph Signaling and Cryptococcus Neoformans Virulencementioning
confidence: 99%